2010 East-West Design &Amp; Test Symposium (EWDTS) 2010
DOI: 10.1109/ewdts.2010.5742054
|View full text |Cite
|
Sign up to set email alerts
|

Fault grading using Instruction-Execution graph

Abstract: Functional test sequences are used in testing to target faults that are not detected by structural test. However, evaluating the stuck-at fault coverage of the functional test sequence by the gate-level fault simulation can be very time consuming. To obtain a fast estimation of the fault coverage, we describe a metric to grade the test sequence using Instruction-Execution graph. The metric is based on the set of registers the circuit traverses under the test sequence. Using this information in combination with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Alternatively, it is possible to use test sequences that were generated as part of a simulation-based design verification process. In this case, either various metrics [11], [12], [13], [14] are suggested how to select the appropriate test sequences from the large verification test pool or selection procedures [16], [17] are proposed in order to improve the effectiveness of the existing functional test sequences.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, it is possible to use test sequences that were generated as part of a simulation-based design verification process. In this case, either various metrics [11], [12], [13], [14] are suggested how to select the appropriate test sequences from the large verification test pool or selection procedures [16], [17] are proposed in order to improve the effectiveness of the existing functional test sequences.…”
Section: Related Workmentioning
confidence: 99%
“…Vinutha et al [14] described a metric to grade the test sequence using instructionexecution graph. The metric is based on the set of registers the circuit traverses under the test sequence.…”
Section: Related Workmentioning
confidence: 99%
“…The functional test sequences are long [8] and it is very time-consuming to evaluate the quality of functional test sequences by gate-level fault simulation. Several authors [12,13,14] suggested estimating the fault coverage of functional test sequences without fault simulation.…”
Section: Related Workmentioning
confidence: 99%
“…Vinutha et al [14] described a metric to grade the test sequence using instruction-execution graph. The metric is based on the set of registers the circuit traverses under the test sequence.…”
Section: Related Workmentioning
confidence: 99%